Anaesthetic challenges in carotid body tumour resection: a case report and review of literature - Malliwal, Anuradha; Mohite, Shubha N.; Doshi, Nishma; Bakhshi, Rochana (International Journal of Research in Medical Sciences, 2017)
Carotid body tumour (CBT) is an extremely rare, non-chromaffin paraganglioma arising from chemoreceptor cells at the carotid bifurcation. Reported incidence is 1-2 per 100,000. Surgical excision of the tumour, the definitive treatment, poses several anaesthetic challenges and a high incidence of perioperative morbidity and mortality (20-40%). Very few cases have been reported so far. We report the anaesthetic management of a case of CBT excision with a review of recent literature on the same.